Evaluating Scuffing Failure in Dry Sliding Conditions of Monolayer Chromium Piston Ring/Bulk Grey Cast Iron Liner Interface - Syed Danish Fayaz (Japanese Society of Tribologists, 2020)
This research reports the scuffing failure phenomenon of piston ring–cylinder liner in pilot state bench tests. Initially, microhardness evaluation of chromium sprayed piston rings of functionally graded Aluminium A390 piston was conducted using a Vickers hardness Indenter following ASTM E-384 standard. The tribological characterization for dry sliding, simulating lubrication starvation was evaluated using reciprocating Universal Tribometer. For surface morphology and allied surface characterization, Energy Dispersive X-Ray spectroscopy integrated Scanning Electron Microscope was used. Substantially large volumes of wear depicting abnormal wear have been observed on the tribo-conjugate grey CI cylinder liner surfaces in sliding with chromium coating on SAE9254 grade steel substrate. This can be attributed to the considerable hardness gradient of tribopair in conjugation. With chromium coating having a conspicuous hardness edge over the CI cylinder liner, the extrusion and ploughing of the liner surface depict the abnormality in wear. The Coefficient of Friction (COF) under dry sliding with stepped load increments showed an unsteady state of friction and this performance is underrated for operation of any tribological system.